Environmental Management Accounting dan Eco-Innovation terhadap Kinerja Keuangan Berkelanjutan melalui Efisiensi Biaya - Mahyudin Mahyudin; Martin Martin; Mardiah Hasanah Nasution (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research was conducted to examine how Environmental Management Accounting (EMA) and Eco-Innovation affect Sustainable Financial Performance, with Cost Efficiency acting as a mediating variable among SMEs in Medan City. A quantitative method with an explanatory research framework was applied in this study. The research population included 341 culinary SMEs officially registered at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Medan City. By applying the Slovin formula, 184 respondents were selected as the research sample. Data were gathered through questionnaire distribution using a Likert-scale measurement. The analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings show that Eco-Innovation positively and significantly influences both Cost Efficiency and Sustainable Financial Performance. In addition, Cost Efficiency was found to positively contribute to Sustainable Financial Performance. Environmental Management Accounting also demonstrated a positive and significant impact on Cost Efficiency; however, its direct relationship with Sustainable Financial Performance was negative though still statistically significant. Moreover, Cost Efficiency was proven to mediate the effect of Eco-Innovation on Sustainable Financial Performance and also mediate the relationship between Environmental Management Accounting and Sustainable Financial Performance. Overall, the results suggest that adopting eco-friendly innovations alongside environmental management accounting practices can strengthen operational efficiency and support the long-term financial sustainability of SMEs.